Dissecting the complexity of CNV pathogenicity: insights from Drosophila and zebrafish models. (June 2021) - Yusuff, Tanzeen; Kellaris, Georgios; Girirajan, Santhosh; Katsanis, Nicholas
Abstract : Genetic architecture predisposes regions of the human genome to copy-number variants, which confer substantial disease risk, most prominently towards neurodevelopmental disorders. These variants typically contain multiple genes and are often associated with extensive pleiotropy and variable phenotypic expressivity. Despite the expansion of the fidelity of CNV detection, and the study of such lesions at the population level, understanding causal mechanisms for CNV phenotypes will require biological testing of constituent genes and their interactions. In this regard, model systems amenable to high-throughput phenotypic analysis of dosage-sensitive genes (and combinations thereof) are beginning to offer improved granularity of CNV-driven pathology. Here, we review the utility of Drosophila and zebrafish models for pathogenic CNV regions, highlight the advances made in discovery of single gene drivers and genetic interactions that determine specific CNV phenotypes, and argue for their validity in dissecting conserved developmental mechanisms associated with CNVs.